Mediatization of Da'wah Hadith in the Digital Age: An Analysis of @risyad_bay's TikTok Account - Zulfirman Manik; Annisa Br. Munthe; Mhd. Fakhrianda Zusrika Rambe; Roby Hanifan Hidayah Siregar; Tiara Karlia Salsabila (Sufiya Journal of Islamic Studies, 2024)
The phenomenon of digital da'wah has grown rapidly alongside the increasing use of social media as a new platform for conveying Islamic messages, including hadith. This study examines how the process of hadith mediatisation is carried out through the TikTok account @risyad_bay. The main issue explored is how hadiths are mediated and repackaged into short-form content for digital audiences. This research was conducted to address the academic need to understand the transformation of hadith transmission in virtual spaces, which differ significantly from traditional da'wah settings. The study aims to uncover the forms of hadith presentation, da'wah communication strategies, and the implications of mediatisation on religious understanding among users. The theoretical framework employed includes the theory of religious mediatisation and digital da'wah communication. The method used is qualitative content analysis of TikTok videos uploaded by the account @risyad_bay over a specific period. The findings indicate that hadiths are presented contextually, accompanied by engaging visual elements, and delivered in a communicative style relatable to younger audiences. This mediatisation process contributes to the popularization of hadith values, although it also poses a risk of meaning simplification. The study concludes that hadith mediatisation on TikTok is an adaptive and effective da'wah strategy, yet it requires deeper interpretive efforts to maintain religious depth.